1983
DOI: 10.1099/0022-1317-64-5-1031
|View full text |Cite
|
Sign up to set email alerts
|

Genome Differences among Varicella-Zoster Virus Isolates

Abstract: The DNAs of 17 isolates of varicella-zoster virus (VZV) were analysed by restriction endonuclease cleavage and agarose gel electrophoresis. By comparing gel patterns of DNAs cleaved with only a few enzymes, all epidemiologically distinct isolates were shown to be unique. Two isolates recovered from members of a family infected in a common-source outbreak were identical to each other (4/4 enzymes) but distinct from the other strains. In addition, three isolates recovered at different times during the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
0
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 11 publications
3
61
0
1
Order By: Relevance
“…Relatively consistent restriction enzyme digestion profiles for different VZV strains were observed, providing the first evidence that VZV has a highly conserved genome. Intrastrain variation in restriction enzyme fragment profiles among wild-type VZV isolates was observed (22,36,37). However, the most prominent differences were linked to variation in the number and composition of VZV genome repeat elements (23,39,40,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively consistent restriction enzyme digestion profiles for different VZV strains were observed, providing the first evidence that VZV has a highly conserved genome. Intrastrain variation in restriction enzyme fragment profiles among wild-type VZV isolates was observed (22,36,37). However, the most prominent differences were linked to variation in the number and composition of VZV genome repeat elements (23,39,40,41).…”
mentioning
confidence: 99%
“…Early efforts in VZV typing used DNA restriction fragment length polymorphism (RFLP) analysis (13,37,38), an approach that confirmed the identity of the VZV strain that causes varicella on primary infection and later reactivates to cause zoster. Relatively consistent restriction enzyme digestion profiles for different VZV strains were observed, providing the first evidence that VZV has a highly conserved genome.…”
mentioning
confidence: 99%
“…These methods were found to distinguish viruses from different geographic regions and have been used to differentiate between the live attenuated Japanese Oka vaccine strain and wild-type viruses circulating in the United States and United Kingdom (17,21,23,29,47). Distinctive restriction enzyme patterns have also allowed differentiation between epidemiologically unrelated viruses, while viruses occurring in a single outbreak have been shown to be identical (20,41). The establishment of latency by the virus in the dorsal root ganglion does not appear to affect the genotype, as evidenced by the identical restriction enzyme profiles of the infecting and reactivating strain from a single individual (42).…”
mentioning
confidence: 99%
“…In the Dumas strain, it contains only one complete and one partial copy of the reiterated element, and was shown to be a true reiteration by examination of other VZV strains . R4 and R5 appear not to code for protein, whereas the elements that make up the other three reiterations are multiples of three bp and are (Oakes et al, 1977;Richards et al, 1979;Ecker & Hyman, 1981 ;Zweerink et al, 1981;Straus et al, 1981Straus et al, , 1983Straus et al, , 1984Martin et al, 1982;Pichini et al, 1983;Vlazny & Hyman, 1985;Hayakawa et al, 1986;Hondo et al, 1987;Kinoshita et al, 1988;. Although loss or gain of restriction sites has been reported (Hondo et al, 1987), the principal form of genomic heterogeneity is due to size variation of restriction endonuclease fragments at discrete locations in the genome.…”
Section: A J Davisonmentioning
confidence: 99%
“…Although loss or gain of restriction sites has been reported (Hondo et al, 1987), the principal form of genomic heterogeneity is due to size variation of restriction endonuclease fragments at discrete locations in the genome. With the advent of restriction endonuclease maps (Ecker & Hyman, 1982;Straus et al, 1982Straus et al, , 1983Davison & Scott, 1983;Gilden et al, 1983;Mishra et al, 1984), these locations were shown to correspond to each of the reiterations (Straus et al, 1983;Hayakawa et al, 1986;Hondo et al, 1987;Kinoshita et al, 1988;. Size heterogeneity is due to variation in the numbers of repeated elements present in the reiterations.…”
Section: A J Davisonmentioning
confidence: 99%